Development and validation of an LC-MS/MS method for simultaneous quantification of voriconazole and its main metabolite voriconazole N-oxide in human plasma and its clinical application. Issue 20 (14th December 2017) - Lei, Meng; Yao, Hongping; Dong, Yalin; Wang, Maoyi; Wang, Zheng; Cheng, Xiaoliang
ABSTRACT: An LC-MS/MS method was developed for simultaneous determination of voriconazole and its main metabolite voriconazole N -oxide in human plasma. Plasma pretreatment was simple one-step protein precipitation with acetonitrile, and separation was achieved on a Hypersil GOLD aQ column. A triple-quadrupole tandem mass spectrometer with electrospray ionization source was operated by multiple reaction monitoring (MRM) in positive ion mode, and the precursor–product ion pairs used for MRM were m / z 350.1→281.0, 365.8→224.1, and 531.3→489.2 for voriconazole, voriconazole N -oxide, and internal standard, respectively. The total analytical run time was 6 min. The proposed method was linear over the range 0.001–1 µg/mL for voriconazole and voriconazole N -oxide. The lower limit of quantification was 1 ng/mL for both of them. The specificity, accuracy, precision, recovery, matrix effect, stability as well as dilution integrity of this method were within acceptable limits during validation period. This method was successfully applied to therapeutic drug monitoring of voriconazole and to evaluate its metabolite profile. GRAPHICAL ABSTRACT: